HUBUNGAN KARAKTERISTIK IBU DAN PEMBERIAN IMUNISASI DENGAN STATUS GIZI ANAK BATITA UMUR 1-3 TAHUN DI DESA TANJUNG BERINGIN KABUPATEN DAIRI TAHUN 2016 - mey sari sibarani; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Every child should receive the basic immunizations before the age of 12 months. The completeness of immunizations can prevent toddler from infectious diseases, moreover, it can also improve their nutritional status. The implementation of immunizations in Puskesmas Pegagan Julu II Tanjung Beringin 2015 has not reached the national standard, which is 80%. Based on data from Puskesmas Pegagan Julu II Tanjung Beringin 2015 the percentage of severe malnutrition on toddlers is 6,13% and the malnutrition is 18,40%. The purpose of this research is to know about the correlation between the characteristics of mothers by giving immunizations and the nutritional status of toddlers aged 12-36 months in Desa Tanjung Beringin Kabupaten Dairi 2016. This non-experimental study using observational analytic method with Cross - Sectional approach. The population in this research were 245 toddlers ranged between aged 12-36 months were recorded in Puskesmas Pegagan Julu II Tanjung Beringin 2015. The research’s samples were 71 toddlers aged 1-3 years. The sampling technique using Purposive Sampling. Data were collected by questionnaire. The collected data were processed and analyzed using computer. The results showed that there was no significant correlation between the age of the mother (p = 0,479), the education of mother (p = 0,429), the occupation of mother (p = 0,429), the number of the toddlers (p = 1,000) and sex of toddlers (p = 0,295) with the nutritional status of the toddlers. There is a relationship between toddler’s age with toddler’s nutrition status (p = 0,043). In 2016 more toddlers who are have good nutrition (87,3 %) than less (12,7 %). The conclusion of this research is there no significant correlation between mother’s characteristics with the nutritional status of toddlers in Desa Tanjung Beringin Kabupaten Dairi 2016. The suggestions is, to increase the monitoring activity, the assessment of the nutritional status and to provide nutrition consultation guidance for mother of toddler were done routinely by health workers in order to improve the nutritional status of the toddler. Keyword : Mother’s Characteristics, Immunization, Nutritional Status